Learning maharah al-kalam through verb and noun forming using the Qiyas method - Chairani Astina; Umi Baroroh; Rifqi Aulia Rahman (Indonesian Journal of Arabic Studies, 2022)
One of the inhibiting factors for learning Maharah Kalam is the lack of students'mufradat treasury. They are only taught conversational material which will be practiced in a literal way or exactly as exemplified by the previous teacher. These barriers are exacerbated by the lack of teacher innovation in designing learning methods that make them active and innovative in producing, deriving, and comparing words, both Isim and fi'il. Whereas in the terminology of the basics of Arabic language, the Qiyas method is known whose main function is to find the origin of the word and then find other forms (sigat) with different positions, functions, and meanings. In this paper, the author uses a literature review with the type of qualitative research, the approach used is descriptive-analytic. The data analysis technique is content analysis. The results obtained by the authors from literature reviews and descriptive-analytic studies, reflect that the qiyas method makes students more active and innovative in producing derived words (furu') from the origin of the word (ashl) based on wazan ('illah) guidelines. In addition, learning maharah kalam is also more efficient because there will be more time available for intensive hiwar practice, because the teacher assigns exploration of this derivative mufradat outside the classroom. While the focus of learning in class is language activities such as hiwar, munaqasyah and munadharah.